2017
DOI: 10.1016/j.jmoldx.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study and Analytical Verification of PCR Methods for the Diagnosis of Congenital Chagas Disease

Abstract: Congenital infection is currently the first cause of new cases of Chagas disease in Argentina and nonendemic areas worldwide. Its diagnosis is of utmost importance to guarantee curative treatment. To improve such diagnosis, a transfer process of PCR tests to the national laboratory network has been initiated. We performed a comparative study of four PCR assays [two end-point PCR and two duplex real-time quantitative PCR (qPCR) procedures] to detect Trypanosoma cruzi DNA in blood samples. Because satellite DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…T. cruzi nucleic acid amplification by PCR has been utilized since 1998 (Russomando et al., 1998) for the detection of T. cruzi in congenitally infected babies, offering a higher sensitivity and specificity than parasitological methods involving direct microscopic examination of blood buffy coat samples (Schijman et al., 2003; Virreira et al., 2003; Mora et al., 2005). Later, qPCR technology was developed (Piron et al., 2007; Virreira et al., 2007; Duffy et al., 2009, 2013; Ramírez et al., 2015) and was able to detect 0.85 or 0.43 parasite equivalents per mL (Pe/mL) of satellite DNA and kinetoplastid DNA, respectively, providing more sensitivity than the conventional PCR technique (Cura et al., 2017). qPCR emerged as a potential tool for an accurate and early diagnosis of congenital T. cruzi infection (Virreira et al., 2007; Bua et al., 2013).…”
Section: Molecular Approaches For the Parasitological Diagnosis Of Thmentioning
confidence: 99%
“…T. cruzi nucleic acid amplification by PCR has been utilized since 1998 (Russomando et al., 1998) for the detection of T. cruzi in congenitally infected babies, offering a higher sensitivity and specificity than parasitological methods involving direct microscopic examination of blood buffy coat samples (Schijman et al., 2003; Virreira et al., 2003; Mora et al., 2005). Later, qPCR technology was developed (Piron et al., 2007; Virreira et al., 2007; Duffy et al., 2009, 2013; Ramírez et al., 2015) and was able to detect 0.85 or 0.43 parasite equivalents per mL (Pe/mL) of satellite DNA and kinetoplastid DNA, respectively, providing more sensitivity than the conventional PCR technique (Cura et al., 2017). qPCR emerged as a potential tool for an accurate and early diagnosis of congenital T. cruzi infection (Virreira et al., 2007; Bua et al., 2013).…”
Section: Molecular Approaches For the Parasitological Diagnosis Of Thmentioning
confidence: 99%
“…This should therefore be born in mind when hematological patients are included in studies of this kind. In fact, Duffy et al [ 40 ] suggested the use of a heterologous extrinsic IAC, which has subsequently been taken up in other studies [ 42 , 51 , 52 ]. Likewise, the RealCycler assay includes this kind of control among the reagents supplied with the kit.…”
Section: Discussionmentioning
confidence: 99%
“…8 Congenital infection of T. cruzi is now the first cause of new cases of Chagas disease in Argentina. 24 The number of CCD cases is used to estimate the burden of congenital transmission; however, there is another key parameter that should be considered when planning and assessing CCD control programmes: the number of babies that should be tested. The number of children born to infected mothers is significantly larger than the number of CCD cases as the transmission rate of T. cruzi from mother to child is around 5% (95% CI 4% to 6%) in endemic countries.…”
Section: Burden Of Ccd and Number Of Newborns That Should Be Tested Fmentioning
confidence: 99%
“…Up to 100% sensitivity has been reported in the detection of T. cruzi in neonates within the first 3 months of age, which qualifies PCR for early-stage diagnosis of CCD. 24 35–37 However, PCR may not be ideal in cases of CCD without persistent parasitaemia, and as a result, sampling at different time points from birth may be needed. 38 A cohort study in an endemic setting in Bolivia that included PCR in the algorithm for detecting vertical transmission of Chagas disease demonstrated its superiority over serology and microscopy.…”
Section: Implementation Of Molecular Tools To Test For Congenital Chamentioning
confidence: 99%